(untitled) (Al-Academy, 2023)
The researcher used the experimental approach due to its suitability and the nature of the research problem. The research community was represented by the eighth-grade students in the Rozak Elementary Mixed School affiliated with the General Directorate of Education in Erbil / the center, for the academic year (2021-2022), the number is (96) students, and the research sample consisted of (63) male and female students, with (31) in the experimental group, and (32) in the control group, and (11) students were excluded by (5) students from the experimental group, and (6) students from the control group, as the excluded, are students who failed and were absent from the lessons, and accordingly, the research sample became composed of (52) male and female students, by (26) male and (26) female students, and to collect information, an achievement test was built for the subject the date, And then it was applied after the availability of scientific conditions in it, and the data were processed statistically using the arithmetic mean, standard deviation, percentage, coefficient of difficulty of objective items, coefficient of ease of objective items, discriminatory power of objective items, Pearson correlation coefficient, Spearman-Brown equation, Guttmann coefficient, The post-test for two independent samples, and the researcher concluded the following:- The students of the experimental group, which is taught according to the strategy of dramatizing characters, excelled in the achievement test of history over the students of the control group, which is taught according to the method used in teaching